Peningkatan Pembelajaran Mengenal Bangun Datar Melalui Model Pembelajaran Project Based Learning Bagi Siswa Tunagrahita - Maurelia, Adinda; Nurhastuti, Nurhastuti; Agusta, Rini (Jurnal Penelitian Pendidikan Khusus, 2023)
This research is motivated by the problems found in SLB Negeri 1 Padang, specifically in the case of  a mental retardation in class IX C who have low learning outcomes in terms of recognizing two-dimensional figures. Based on the assessment results, it was found that students faced difficulties in school activities such as recognizing two-dimensional figures like squares, rectangles, triangles, and circles. The aim of this research is to improve the process and learning outcomes of recognizing two-dimensional figures through the implementation of Project-Based Learning. The research method used is Classroom Action Research, consisting of two cycles. Based on the research results, the use of the Project-Based Learning model is effective in improving the learning outcomes of plane geometry. This is evident from the increased learning outcomes of the students in each cycle.